Alabama : Poems - Jones, Rodney, 1950- (Book collections on Project MUSE., 2023)
"In the wake of a cancer diagnosis, the death of his parents, and the election of Donald Trump, Pulitzer finalist and National Book Critics Circle Award winner Rodney Jones began writing Alabama. Encompassing labyrinth, meditation, fable, and peasant poem, formed from interleaved strands of prose vignettes and lineated poetry-if it is his darkest book, his playfulness and lyrical panache transmute the heartbreak. A new sweetness and intimacy pervades the work, a sense of relaxing into his voice, and a vision as clear as top-shelf moonshine, rooted in love, grounded in an abiding awareness of mortality of both person and place. On one level, the book takes a hard look at globalization as negotiated by a single rural enclave long vulnerable to the whims of multinational capitalism. At the same time, there's an embrace, often elegiac, of what fastens us to place, to the land and the people who work it. All shaped by Jones's deep empathy and feeling for wiry and strong character, rendered in compelling narratives as local as they are universal, and permeated with his wonderfully sardonic, enduring humor. Alabama offers readers language played masterly by the poet who Dan Chiasson, writing in Poetry, called "the best accessible poet writing in America.""--